Answer:
Explanation:
Simplifying
2x + -1 = 7x + -8
Reorder the terms:
-1 + 2x = 7x + -8
Reorder the terms:
-1 + 2x = -8 + 7x
Solving
-1 + 2x = -8 + 7x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-7x' to each side of the equation.
-1 + 2x + -7x = -8 + 7x + -7x
Combine like terms: 2x + -7x = -5x
-1 + -5x = -8 + 7x + -7x
Combine like terms: 7x + -7x = 0
-1 + -5x = -8 + 0
-1 + -5x = -8
Add '1' to each side of the equation.
-1 + 1 + -5x = -8 + 1
Combine like terms: -1 + 1 = 0
0 + -5x = -8 + 1
-5x = -8 + 1
Combine like terms: -8 + 1 = -7
-5x = -7
Divide each side by '-5'.
x = 1.4
Simplifying
x = 1.4